Effect of quality of carnauba wax (Copernica cerífera) on microstructure, textural, and rheological properties of soybean oil-based organogels. (January 2021) - Buitimea-Cantúa, Génesis V.; Serna-Saldívar, Sergio O.; Pérez-Carrillo, Esther; Jordânia Silva, Thais; Barrera-Arellano, Daniel; Buitimea-Cantúa, Nydia E.
Abstract: This work was designed to elaborate soybean oil organogels structured with three different types (T-I, T-III, and T-IV) of carnauba wax, aiming to find the best wax type and concentration for application in foods. Carnauba wax T-I and T-III produced gels Type 5 (firm and no oil release) at lower concentration (4.5% w/w) in comparison to T-IV (5.0% w/w). Thermal stability of wax T-III at 4% w/w organogel was higher in comparison to T-I and T-IV; however, all waxes at >5.5% w/w formed organogel type 5. Color parameters L *, a *, and b * were directed related to wax type. The polarized light microscopy revealed that organogels formed two different crystal morphologies post-crystallization as a result of Ostwald ripening. Organogels stored for 24 h showed a condensed display of crystals, whereas those stored for 2 months cluster crystalline particles. The hardness of 24 h stored organogels was the same ( p  < 0.05) for all carnauba waxes (T-I = 0.13 N, T-III = 0.18 N, and T-IV = 0.06 N) whereas counterparts stored for 2 months the hardness values were significantly ( p  < 0.05) higher (T-I = 0.22 N, T-III = 0.28 N, and T-IV = 0.10 N). Carnauba wax T-III at 4% w/w showed excellent properties for diverse food applications. Highlights: Soybean oil structured with 5.5% carnauba waxes yielded solid organogels with high thermal stability. Time storage increased shear stress of organogels especially those produced with type I carnauba wax. Organogels stored for two months produced cluster crystalline particles. Organogels stored for 2 months were comparatively harder compared to counterparts stored for 24 h.